PENERAPAN KAHOOT PADA MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN MINAT SISWA KELAS X3 SMA PANJURA - Alief Dean Rama; Alfi Sahrina; Sri Wulandari (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2025)
This study aims to address the issue of low student interest in learning in class X3 at SMA Panjura, which impacts their learning outcomes. Students often perceive geography as a monotonous and difficult subject, which reduces their involvement and active participation in the learning process. To overcome this issue, this research implements the interactive Kahoot media based on Problem-Based Learning (PBL) to improve both student interest and the effectiveness of the learning model used in class. PBL encourages students to actively solve real-world problems collaboratively, while Kahoot incorporates gamification elements to increase student engagement. The method used in this study is Classroom Action Research (CAR), conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Data was collected through Kahoot quizzes, observations, and student interest questionnaires. The results show a significant improvement in both student interest and learning outcomes. Before the implementation of PBL with Kahoot (pre-action), student interest was at 55%. In the first cycle, 80% of students gave positive feedback on Kahoot, although some students felt anxious due to the time limitations and unfamiliarity with the technology. In the second cycle, student interest increased to 92% after the addition of collaborative elements and rewards. The increase in student interest from pre-action (55%) to the second cycle (92%) shows a significant improvement of 37%. These results indicate that the use of Kahoot in PBL successfully enhanced student engagement, interest, and the effectiveness of the learning process.